Relacje państwo – Kościół w czasach stalinizmu (1948–1953) w świetle publikacji „Tygodnika Powszechnego” i „Trybuny Ludu” - Stawarz, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 2014)
The aims of the article is to discuss the difficult and complicated relationship between the Church and the communist regime in Poland after World War II in the light of two antithetical press titules: „Tygodnik Powszechny” and „Trybuna Ludu”. The choice quotations in such a way that they have fully bring the prevailing atmosphere in the pages of these magazines during the period. Important role in establishing relations with the government of the relationship of the Church played a new Polish Primate – Stefan Wyszyński who led the Church in Poland during the grounbreaking for the nation and the country.